Ultrasonic Waves Assisted Synthesis of Curcuminoids Based on 3-Methylacetylacetone and in Situ Synthesis of Gold Nanoparticles Capped with Curcuminoids - Saeed, Bahjat A.; Neamah, Faiz O.; Elias, Rita S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
Ultrasonic irradiation was used to induce the Knuevenagle reaction between aromatic aldehydes and 3-methylacetylacetone to synthesize curcumin analogues with moderate to good yields. The structures of the compounds were established by elemental analysis and from their mass and 1HNMR spectra. In situ curcumin-gold nanoparticles were synthesized. The solutions of the prepared nanoparticles have purple to deep-red colors and their UV-vis spectra were characterized by the Surface Plasmon Resonance bands within the range 538-554 nanometer.